Can crowdsourcing produce better products than a single visionary. - Whong, Jason
Ben Kaufman was just 21 when he became the head of an iPod accessory company.Now he's out to prove that awesome products can be born from the collective brain power of people far and wide.
Keywords: Kaufman, Ben; Quirky; Split Stick